2020
DOI: 10.1016/j.omtn.2020.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal Delivery of AntagomiRs Targeting Viral and Cellular MicroRNAs Synergistically Inhibits Cancer Angiogenesis

Abstract: Nasopharyngeal carcinoma (NPC) is an Epstein-Barr virus (EBV)-associated cancer characterized by a high degree of recurrence, angiogenesis, and metastasis. The importance of alternative pro-angiogenesis pathways including viral factors has emerged after decades of directly targeting various signaling components. Using NPC as a model, we identified an essential oncogenic pathway underlying angiogenesis regulation that involves the inhibition of a tumor suppressor, Spry3, and its downstream targets by EBV-miR-BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 45 publications
(50 reference statements)
0
29
0
Order By: Relevance
“…For exosome-mediated paracrine signaling, NPC-derived exosomes have been reported to either enhance or suppress angiogenesis upon uptake by HUVECs due to exosomal delivery of functional biomolecules [48][49][50]. Our Matrigel plug assay indicated that treatment with LBH+ exosomes decelerated in vivo angiogenesis.…”
Section: Discussionmentioning
confidence: 75%
“…For exosome-mediated paracrine signaling, NPC-derived exosomes have been reported to either enhance or suppress angiogenesis upon uptake by HUVECs due to exosomal delivery of functional biomolecules [48][49][50]. Our Matrigel plug assay indicated that treatment with LBH+ exosomes decelerated in vivo angiogenesis.…”
Section: Discussionmentioning
confidence: 75%
“…Huang and colleagues [17] using the clinicopathological data of 1286 NPC patients found that the degree of differentiation of NPC tumor cells was closely related to their biological behavior, and affected tumor staging, lymph node metastasis and treatment, which consequently led to various prognosis in NPC patients. In addition, other domestic and international studies found that the degree of differentiation of nasopharyngeal carcinoma tumor cells was closely related to the degree of malignancy, and affected the survival and prognosis of patients [18][19][20]. The higher the differentiation of nasopharyngeal carcinoma tumor cells had the better the prognosis of patients..…”
Section: Summary Of Main Ndings In This Studymentioning
confidence: 95%
“…EBV-related products in the exosomes of NPC can also affect tumor progression, such as the EBV-encoding RNAs (EBERs). For instance, EBERs regulate the expression of vascular cell adhesion molecule 1 (VCAM-1) through TLR3/RIG-I to induce angiogenesis 47 ; EBV-miR-BART10-5p and miR-18a strongly promote angiogenesis and tumor growth of NPC by mediating the expression of VEGF and HIF1-α in a Spry3-dependent manner 48 . More important, the exosomal molecules not only have the ability to accelerate angiogenesis but also hold inhibitory functions.…”
Section: Exosomes Affect Various Processes Of Npcmentioning
confidence: 99%
“…In NPC, a number of key regulatory molecules involved in the tumor pathological process have been identified and a few of them have been used for novel cancer immunotherapy in vitro or in vivo . A research team has worked to incorporate antagomiR targeting BART10-5p and miR-18a (which are intended to promote angiogenesis) into iRGD-tagged exosomes, resulting in preferentially suppressed angiogenesis and growth of NPC 48 . Delivering miR-34c (a tumor suppressor of NPC) to the cancerous cells through mesenchymal stem cell exosomes can impede β-chain protein and slow down the invasion, metastasis, proliferation and EMT of NPC cells, ultimately inhibiting tumor deterioration and radiation resistance 5 .…”
Section: Npc-related Exosomes In Clinical Applicationmentioning
confidence: 99%